Effect of two years of calorie restriction on liver biomarkers: Results from the CALERIE phase 2 randomized controlled trial. - Dorling, James L. (Eur J Nutr, 2020)
PURPOSE: Calorie restriction (CR) is an effective treatment for obesity-related liver and metabolic disease. However, CR studies in individuals without obesity are needed to see if CR could delay disease onset. Liver biomarkers indicate hepatic health and are linked to cardiometabolic disease. Our aim was to examine the effects of a two-year CR intervention on liver biomarkers in healthy individuals without obesity. METHODS: The Comprehensive Assessment of Long-term Effects of Reducing Intake of Energy (CALERIE) study was a two-year randomized controlled trial. Overall, 218 participants (body mass index: 25.1±1.7 kg/m(2)) were enrolled into control group (n=75) that ate ad libitum (AL) or a CR group (n=143) that aimed to decrease energy intake by 25%. Alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), gamma-glutamyl transferase (GGT), and bilirubin were measured during the trial. RESULTS: At month 24, relative to the AL group, ALP (−7±1 IU/L; P<0.01) and GGT (− 0.11 ± 0.04 log IU/L; P = 0.02) decreased and bilirubin increased (0.21±0.06 log mg/dL; P<0.01) in the CR group; no between-group differences in ALT (−1±1 IU/L; P>0.99) or AST (2±2 IU/L; P=0.68) were revealed. However, sex-by-treatment-by-time interactions (P<0.01) were observed, with CR (vs. control) inducing reduced ALT and GGT and increased AST in men only (P≤0.02). CONCLUSIONS: In metabolically healthy individuals without obesity, two years of CR improves several liver biomarkers, with potentially greater improvements in men. These data suggest that sustained CR may improve long-term liver and metabolic disease risk in healthy adults. TRIAL REGISTRATION: Clinicaltrials.gov (NCT00427193) Registered January 2007.